Caste and Social Hierarchy in The God of Small Things: Exploring the Impact of Caste and Social Class in 'The God of Small Things' (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The classifications among social classes are highly valued in India. Occupation and socialconduct were used to define distinct social classes. No one can predict that these social evils willdisappear from human civilization any time soon, even if we are well into the 21st century. Criticallyacclaimed book The God of small things (1997) by Arundhati Roy catapulted her to internationalrecognition. “The God of Small Things” by Indian novelist and activist Arundhati Roy is the focus on theanalysis of caste system in society. The piece draws attention extensively on Arundhati Roy's Flamingopublishedbook, The God of Small Things. This work not only portrays the class struggles that exist inIndian culture, but also demonstrates the author's sophisticated understanding of the caste system.There are significant parallels between the events of The God of small things and Arundhati Roy's ownlife. The work destabilized the caste system by focusing on a woman's infatuation for a marginalizedcharacter. In every circumstance, the oppressed individual is the one who suffers and is overlooked byeveryone around them. The social status of the characters is examined in light of the notion of socialclass and its supporting characteristics. Using the social class consequences framework, we examinehow the characters' socioeconomic status affects their lives. There are several depictions of the mainprotagonists' socioeconomic status.